Compact UWB FSS reflector for antenna gain enhancement. Issue 10 (1st May 2019) - Yuan, Yanning; Xi, Xiaoli; Zhao, Yuchen
Abstract : In this study, two compact ultra‐wideband (UWB) frequency selective surface (FSS) reflectors, which combine the branch loading method with the design of the traditional FSS, are proposed for antenna gain enhancement application. The working mechanism of the proposed FSS reflectors is analysed by the equivalent circuit model. The first FSS reflector, which is a 10 × 10 array with 8.25 mm × 8.25 mm unit size, not only enhances the gain of the UWB antenna, but also guarantees a constant gain with only 0.5 dB variation across the whole operation band. To further reduce the reflector size, a more compact FSS reflector with 6.25 mm × 6.25 mm unit size is designed by printing similar patterns on both sides of a single‐layer dielectric slab. Compared to the first structure, the second reflector can realise a 25% size reduction and the same gain variation in the entire UWB frequency range. The only compromise is a 0.5 dB gain decrease. Finally, a good agreement between the measured and simulated results proves the feasibility of the authors' design.